1990
DOI: 10.1056/nejm199009063231004
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Corticosteroids in Children with Corrosive Injury of the Esophagus

Abstract: There appears to be no benefit from the use of steroids to treat children who have ingested a caustic substance. The development of esophageal stricture was related only to the severity of the corrosive injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
113
2
19

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(143 citation statements)
references
References 18 publications
9
113
2
19
Order By: Relevance
“…Nos casos de lesões graves (2b e 3) entretanto, há edema, solução de continuidade ou necrose e invariavelmente há invasão bacteriana com proliferação. Quando associado ao corticóide, o antibiótico pode reduzir as complicações decorrentes da imunossupressão 21,22 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Nos casos de lesões graves (2b e 3) entretanto, há edema, solução de continuidade ou necrose e invariavelmente há invasão bacteriana com proliferação. Quando associado ao corticóide, o antibiótico pode reduzir as complicações decorrentes da imunossupressão 21,22 .…”
Section: Discussionunclassified
“…Anderson et al 21 publicaram trabalho prospectivo com 60 crianças que apresentaram lesões esofágicas. Os 18 pacientes grupo com lesões grau 1, tratados ou não com esteróides, evoluíram sem estenose.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Son olarak, yüksek dozajlı steroid kullanımı (dexametazon, 4 ila 6 hafta boyunca, 1 mg/kg) savunulmuştur. Ancak, bu çalışmalardaki hasta sayısı azdır ve özofagusun mikotik enfeksiyonu, osteit, peptik ülserasyon ve osteoporoz gibi komplikasyonlar bildirilmiştir (12).…”
Section: Tedaviunclassified
“…5,6 However, even though steroids have been widely used in various doses in humans since the 1950s, the results have been variable and often disappointing. 5,7 In a prospective study, Anderson et al 8 found that corticosteroid treatment had no significant effect on stricture formation. Conversely, Howell et al 9 reported that corticosteroid therapy reduces stricture development in grade II and III cases based on the analysis of 13 studies.…”
mentioning
confidence: 99%